Cytokines as cellular communicators - R. Debets; H. F. J. Savelkoul (Mediators of Inflammation)
Cytokines and their receptors are involved in the pathophysiology of many diseases. Here we present a detailed review on cytokines, receptors and signalling routes, and show that one important lesson from cytokine biology is the complex and diverse regulation of cytokine activity. The activity of cytokines is controlled at the level of transcription, translation, storage, processing, posttranslational modification, trapping, binding by soluble proteins, and receptor number and/or function. Translation of this diverse regulation in strategies aimed at the control of cytokine activity will result in the development of more specific and selective drugs to treat diseases.